2010
DOI: 10.1001/archoto.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Smad3 Expression in Radiation-Induced Fibrosis Using a Novel Method for Topical Transcutaneous Gene Therapy

Abstract: Smad3 expression can be effectively silenced in vivo using a novel topical delivery system. Moreover, cutaneous Smad3 inhibition mitigates radiation-induced changes in tissue elasticity, restoring a near-normal phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Accordingly, transcutaneous delivery of Smad3 siRNA decreases radiation-induced skin fibrosis as compared with control siRNA. 171 Future studies targeting other components of the TGF-b signaling pathway to modulate wound healing and scarring outcome are eagerly awaited. Figure 8 depicts strategies for targeting the TGF-b pathway to improve wound healing outcome as described earlier.…”
Section: Strategies Used For Targeting the Tgf-b Signaling Pathway Tomentioning
confidence: 99%
“…Accordingly, transcutaneous delivery of Smad3 siRNA decreases radiation-induced skin fibrosis as compared with control siRNA. 171 Future studies targeting other components of the TGF-b signaling pathway to modulate wound healing and scarring outcome are eagerly awaited. Figure 8 depicts strategies for targeting the TGF-b pathway to improve wound healing outcome as described earlier.…”
Section: Strategies Used For Targeting the Tgf-b Signaling Pathway Tomentioning
confidence: 99%
“…Therefore, other effective targets for inhibiting the downstream activity of TGF-b/Smad signaling could be Smad3 or TGF-b receptors, including TGFBRI, TGFBRII, and TGFBRIII. In fact, wound scarring has been shown to be reduced by downregulating expression of Smad3 (Sekiguchi et al, 2007;Wang et al, 2007;Lee et al, 2010) or TGFBRII protein expression (Nakamura et al, 2004;Chu et al, 2008). In addition, overexpression of dominant negative mutant TGFBRII has been used to inhibit TGF-b binding to normal TGF-b receptors (Reid et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al first delivered Smad3 siRNA to inhibit skin fibrosis induced by radiation. 143 Similarly, Wang et al inhibited TGF-b/Smad signaling by applying TGF-b1 receptor siRNA and reported reduced hypertrophic scarring. 144 To sustain the release of these TGF-b/Smad targeting siRNAs, delivery matrices, including trimethyl chitosan 145 and pressure-sensitive hydrogels, 146 were developed.…”
Section: 81mentioning
confidence: 99%